2010
DOI: 10.1021/ja107539j
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Silica-Supported Transition Metal Fragments for Kubas-type Hydrogen Storage

Abstract: To verify the role of the Kubas interaction in transition metal grafted mesoporous silicas, and to rationalize unusual rising enthalpy trends with surface coverage by hydrogen in these systems, computational studies have been performed. Thus, the interaction of H2 with the titanium centers in molecular models for experimentally characterized mesoporous silica-based H2 absorption materials has been studied quantum chemically using gradient corrected density functional theory. The interaction between the titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
50
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 63 publications
(121 reference statements)
12
50
1
Order By: Relevance
“…This functional was chosen because of its success in our previous studies on the benzyl titanium binding sites of a mesoporous silica 14 and on the vanadium binding sites of a hydrazine linked material, 17 and because it has been shown by Sun et al to be the best functional to balance computational speed and accuracy when looking at dihydrogen bound to metal centres. This functional was chosen because of its success in our previous studies on the benzyl titanium binding sites of a mesoporous silica 14 and on the vanadium binding sites of a hydrazine linked material, 17 and because it has been shown by Sun et al to be the best functional to balance computational speed and accuracy when looking at dihydrogen bound to metal centres.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…This functional was chosen because of its success in our previous studies on the benzyl titanium binding sites of a mesoporous silica 14 and on the vanadium binding sites of a hydrazine linked material, 17 and because it has been shown by Sun et al to be the best functional to balance computational speed and accuracy when looking at dihydrogen bound to metal centres. This functional was chosen because of its success in our previous studies on the benzyl titanium binding sites of a mesoporous silica 14 and on the vanadium binding sites of a hydrazine linked material, 17 and because it has been shown by Sun et al to be the best functional to balance computational speed and accuracy when looking at dihydrogen bound to metal centres.…”
Section: Computational Detailsmentioning
confidence: 99%
“…2,[11][12][13][14][15][16][17] Our first computational study was of a storage material based on an experimentally confirmed mesoporous silicate with titanium benzyl binding sites, 11 and the second was a hydrazine linked system containing vanadium binding sites. 2,[11][12][13][14][15][16][17] Our first computational study was of a storage material based on an experimentally confirmed mesoporous silicate with titanium benzyl binding sites, 11 and the second was a hydrazine linked system containing vanadium binding sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by use gen molecules are basically non-polar, but the strong interaction of the metal particles leads to the dipole inducing effects of the hydrogen molecules. The third group and any remaining hydrogen molecules are adsorbed by the same mechanism of high gas pressure, but this equilibrium can be broken when the interaction of oxidized graphite surfaces and dipole-induced hydrogen molecules is stronger than metal-hydrogen interactions [98][99][100][101][102]. This mechanism can be applied only under higher pressure, and when graphite supports are charged strong electron acceptors.…”
Section: Othersmentioning
confidence: 99%
“…11,12 While this behavior has since been disproven by examination of the electronic exchange interaction occurring in similar metal–organic frameworks, 1315 interest in Kubas-type binding has remained for hydrogen storage applications and has led to renewed experimental and theoretical efforts to develop materials exhibiting this effect. 1618 …”
mentioning
confidence: 99%